Future-Proofing Energy Transport Law - Alexandra B. Klass (Washington University Law Review, 2017)
The U.S. energy system is critical to every aspect of the nation’s economy and daily life. That energy system, in turn, is completely dependent on U.S. energy transport infrastructure—the oil pipelines, natural gas pipelines, electric transmission lines, and import and export facilities that transport and distribute the energy resources that power the country. This Article explores how the law can influence the billions of dollars in private sector energy transport investments necessary to meet current energy needs as well as respond to the significant technological, market, and policy developments in the energy sector. In doing so, it develops criteria policymakers should consider in creating laws and regulations to govern energy transport infrastructure that focus on federalism principles, flexibility in the location and amount of energy resources, and clean energy goals. It then applies these criteria to two of the nation’s most pressing energy transport debates: (1) whether to transfer more siting authority for interstate electric transmission lines from the states to a federal or regional authority and (2) whether to transport new sources of North American oil primarily by an upgraded rail system or by expanded pipeline infrastructure.
Keywords: energy transport infrastructure; energy system; energy transport law; federalism; future- proof; fossil fuel and renewable energy resources; oil pipeline; Keystone XL; Dakota Access; Natural Gas; Clean Power Plan; Federal Energy Regulatory Commission; FERC; Advanced battery technology; Department of Energy; Energy Policy Act of 2005